If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-6=6x-2x
We simplify the equation to the form, which is simple to understand
5x-6=6x-2x
We move all terms containing x to the left and all other terms to the right.
+5x-6x+2x=+6
We simplify left and right side of the equation.
+1x=+6
We divide both sides of the equation by 1 to get x.
x=6
| 3b^2-21b+36=0 | | x(x-3)=2 | | r^2-9r+20= | | a^2+7a+6= | | (2.83m^2-2.12n^2)(2.83m^2+2.12n^2)= | | 0.2c-0.6+0.5c=5 | | c^2+6c-16=0 | | 38(x-152)=76 | | 5n-2=23 | | c^2+3c+2=0 | | (5y^2+3z)(5y^2-3z)= | | 4y-8=20 | | (3x-z^2)(4x-3z^2)= | | 7r+2=30 | | 2X+2X=30 | | (2m^2-2n^2)(2m^2+2n^2)= | | 6=s+1 | | s-9=-8 | | 5y^2+28y-12=0 | | 80=10x+6x | | (a^2-3b)(a^2+5b)= | | 8=-4k | | 480=(14+w)(w) | | u^3=-23 | | 49x^2+28x+3=0 | | 8.45+3.3+6=a | | 3x^2-20x+100=0 | | r^2+10tw+2wr-5tr= | | (y+2)(y-2)= | | x+16x=8 | | 178=11x+13 | | (4a-3)(a+2)= |